Analysis of Factors Related to Behavior towards Visual Inspection with Acetic Acid Test among Women of Childbearing Age and Elderly Women - Dewi Novitasari Suhaid; Margaretha Kusmiyanti (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2022)
Cervical cancer is second leading cause of mortality among women. Cervical cancer is caused by Human Papillomavirus (HPV) infection. 70% of patients with cervical cancer come to health services in advanced staged, even though if symptoms are detected earlier. 43% of cancer disease can be prevented and ⅓ of cases can be cured when the symptoms are detected early. The simplest early detection, which effective and efficient for detection of cervical cancer is Visual Inspection with Acetic Acid (VIA) test. However, almost 50% of patients who were diagnosed cervical cancer never had VIA test before. This study aims to analyze factors related to behavior towards VIA test among women of childbearing age and in elderly women. Case control study was conducted among 181 participants based on the inclusion criteria of women aged >15 years old and married or ever had sexual intercourse. Rasch model test, t-test, chi square test and logistic regression were applied to analyze the data. The analysis results showed that there was a significant relationship between the age at first marriage, marriage frequency and knowledge with behavior towards VIA test. An individual’s chance of not having VIA test by criteria of first married age of <20 years old, getting married >1 time, having low motivation and less knowledge was 94%. It can be concluded that knowledge was dominant factor related behavior towards VIA test.